Translating Theory of English into Indonesian and Vice-Versa - Apriyanti, Teti; Wulandari, Heidy; Safitri, Marita; Dewi, Novita (Indonesian Journal of English Language Studies (IJELS), 2016)
The present study is aimed at providing translating theory of English into Indonesian and vice versa. In achieving the aim, content analysis of expressive (poem), informative (report andacademic), and vocative text (advertisement) is applied. The analysis is based on threeaspects consisting of grammatical structure, cultural words, and writing mechanic. The resultshows that the translator needs to adapt the grammatical structure, cultural words, and writingmechanic of source language into target language. However, there are exceptions in culturalwords and capitalization. In translating from English into Indonesian especially in academictext, some English words are assimilated into Indonesian (foreignization). In translatingIndonesian poem into English, the target text capitalization imitates source textcapitalization. Besides, for the purpose of attractiveness, persuasion, and effectiveness intranslating Indonesian advertisement into English, different words are prefered but themeaning is retained. Keywords: translating theory, English, Indonesian